2011
DOI: 10.4274/tjo.41.09719
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Visual Outcomes in Patients Implanted with Acri.LISA 356D Multifocal Intraocular Lens

Abstract: Amaç: Acri.LISA 356D bifokal göz içi lensi implantasyonu yap›lan hastalarda görsel sonuçlar›n de¤erlendirilmesi. Gereç ve Yöntem: Fakoemülsifikasyon tekni¤i ile katarakt ekstraksiyonu yap›lan 26 hastan›n 33 gözüne difraktif multifokal G‹L Acri.LISA 356D implantasyonu yap›ld›. Ameliyat sonras› 1. ve 3. ayda tüm gözlerin ayd›nl›k (85 cd/m 2 ) ortamda ve karanl›k (5 cd/m 2 ) ortamda kontrast duyarl›l›klar›, düzeltmesiz ve düzeltmeli uzak, yak›n ve orta görme keskinlikleri ile gözlük ihtiyaçlar›, refraktif kusurla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, problems such as glare and halo due to multifocal IOLs implanted in the patients with preexisting corneal astigmatism have been frequently encountered in the studies. [7][8][9] Several methods, including changing the site of incision in phacoemulsification, astigmatic keratotomy or limbal relaxation incisions, have been tried during surgery to reduce astigmatism. However, these procedures have restrictions such as long-term mechanical instability and the limited degree of astigmatism that can be corrected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, problems such as glare and halo due to multifocal IOLs implanted in the patients with preexisting corneal astigmatism have been frequently encountered in the studies. [7][8][9] Several methods, including changing the site of incision in phacoemulsification, astigmatic keratotomy or limbal relaxation incisions, have been tried during surgery to reduce astigmatism. However, these procedures have restrictions such as long-term mechanical instability and the limited degree of astigmatism that can be corrected.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] However, it was reported that depth of focus reduces and problems such as blurred vision, photophobia, halo and glare are more prevalent in the patients that underwent multifocal IOL implantation and have uncorrected corneal astigmatism of 0.75 diopter and over. [7][8][9] In addition to correction of refractive defect and enabling near vision without the need for eyeglasses, also correction of astigmatism has been possible with multifocal toric IOL that has been manufactured recently. Accordingly, dependency on eyeglasses following surgery has become less prevalent.…”
Section: Introductionmentioning
confidence: 99%